Results of restoration of complex injuries in ligamentous apparatus of the knee joint - Golovakha, Maksim; Banit, Oleg; Titarchuk, Rostyslav; Zasypko, Igor; Didenko, Inna; Orljanski, Weniamin (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Injuries of multiple ligaments of the knee joint usually occur as a result of high energy trauma. The greatest difficulties one has in choice of tactics in treatment of patients with combined injuries of capsular and ligamentous apparatus of the knee joint. Objective: To determine the most appropriate treatment strategy for patients with complex injuries of the ligaments of the knee joint. Methods: We studied 37 patients (31 men, and 6 women aged 24 to 44 years) with two or more ligaments injuries of the knee joint of varying severity as a result of sport (12) and road traffic (25) injuries. We discovered combined injuries of ligaments: anterior crucial ligament (ACL) and medial collateral — 12; posterior crucial ligament (PCL) and medial collateral — 3; ACL, PCL and both collateral — 15; PCL and lateral collateral — 7. All patients were treated surgically. The outcomes were evaluated in 4 and 6 months after the operation according to scale IKDC and MRI parameters. Results: The most severe injuries are luxations of the shin accompanied by injuries of two crucial ligaments and one or two collateral ligaments. In this case restorative surgical treatment of all damaged structures can be made in the first day after trauma. But due to technical difficulties conservative waiting tactics with staged restoration of ligaments is justified. In the case of fresh or inveterate injury of ACL and PCL it is possible to perform their simultaneous and staged recovery when firstly they restore PCL, and after 3–4 months — ACL. The best results of PCL reconstruction are obtained in case surgical treatment immediately after the injury. Along with the reconstruction of PCL it is necessary to restore posterolateral capsular-ligamentous complex. The combined damages of the medial collateral ligament and one of the crucial ligaments rarely need to restore medial capsular-ligamentous structures. Under condition of restoration of fresh ACL injury almost always they eliminate instability caused by medial collateral ligament injury. In another case after fresh injury it is necessary to perform suturing of disruption place and after inveterate — plasthy of medial part of the knee joint.